The Carrying Capacity Assessment of Two MRTStations Transit-Oriented Development Areas in Jakarta - Hayati Sari Hasibuan; Ahyahudin Sodri; Riza Harmain (Faculty of Geography, Universitas Gadjah Mada, 2021)
Many studies have investigated the effects of transit-oriented development (TOD) on density, design, diversity development, and transit ridership. However, fewer studies address the issue of carrying capacity of TOD. This paper aims to assess TOD areas' carrying capacity using four criteria (land capability, water availability, socio-economic, and green infrastructure) and 14 indicators on Jakarta's two TOD areas. These results show that even though both of the TOD area, Dukuh Atas and Lebak Bulus, are in the good of carrying capacity in land capability, there are some issues to address the possibility of water availability. For TOD's success, the socio-economic criteria should be promoted in the fringe-urban TOD area like Lebak Bulus. We identified the green infrastructure, such as pedestrian, cycling route, and green open space, still in low development and should be pursued to extend the TOD carrying capacity for the future.